An Analysis Of Semantic Roles Of Titles In The Jakarta Post - Ayuningtyas, Chandra; , Dra. Siti Zuhriah Ariatmi, M.Hum; , Dra. Malikatul Laila, M. Hum (2014)
This research aims at describing the roles as in NP construction of the title in the Jakarta Post and describing the denotative and connotative meaning of the title in the Jakarta Post. The research conducted by the writer is descriptive qualitative research. The data of this research are simple declarative sentence of the title in the Jakarta Post newspaper, while the data source is taken from the Jakarta Post newspaper published January 2014. The method used by the writer in collecting the data is documentation with the steps: reading, selecting, collecting, and coding the data. In analyzing the data, the writer describes the role played by NP by referring to the theory of thematic role by O'Grady (1987) and describes the meaning of the sentence found in title of the Jakarta Post newspaper by referring to the denotative and connotative meaning. The result of this research shows that there are twenty one patterns that are classified into three roles in the starting sentence. They are agent (88 data/85,45 %), theme (4 data/3,88 %), and experiencer (11 data/10,67 %). NPs 1 functioning as agent and experiencer when the type of simple declarative sentence is active sentence, while NPs1 functioning as theme when the type of simple declarative sentence is passive sentence. The writer analyzes the meaning by referring to the denotative and connotative meaning. By denotative meaning the writer explains paraphrasing or re-construction, while by using connotative meaning the writer explains using personal aspect and intercontextuality of the sentence. The result of data analysis in the case of denotative and connotative meaning by using paraphrasing or reconstruction is that the meaning of the titles in the Jakarta Post is more clearly and comprehensive, not only the meaning of the words but also show the aspect of personal and intercontextuality